Comparison between the British and American Methods in Designing Concrete using Local Aggregate in the City of Mosul Preparation - Mohammed Taher Abdul Rahman Al-Haidari (International Journal of Engineering and Management Research, 2021)
This research included an applied study for the design of concrete mixtures by following the method of the American Concrete Institute (ACl) and the method of the Building Research Center in England (British method) to restriction which of these two methods is more suitable for use and application in the design of concrete mixtures when using local aggregate (gravel and sand taken from the area Badush and Aski Mosul), where job mixes were made using the mixing ratios obtained from these two methods, and a comparative study was made for the properties concrete resulting in the soft state (workability )and the hardened state (compressive resistance), and the results proved the following: A- In general, when discussing the results according to mixing ratios and workability levels, the method of the Building Research Center in England (the British method) gave higher results than the results obtained by the American Concrete Institute method (the American method) when using the above local aggregate whereas results shown increase in (workability) and Compressive strength. This increase amounts to the percentages shown in the table below: Compressive strength (%) Slump test (%) workability 10.48 14.40 Precipitation = 10-8 cm 12.10 21.40 Precipitation = 18-15 cm Table (1-1) B- It is possible to make another comparison, when fixing the proportion of water/cement, it turns out that the method of the Building Research Center in England (the British method) gives higher workability than the method of the American Concrete Institute (the American method) and for the same proportion of cement/ water, the American method gives Higher compressive strength than the British method. C- The building research center method is a more practical and applicable method more than the American Concrete Institute method because it takes the type of cement, the type of aggregate and other properties of the aggregate (especially particle shape) into consideration more than it is in the American Concrete Institute (ACI) method. The above results were relied upon in designing the appropriate concrete mixture in the Mosul Water Project - Right Coast.